2019
DOI: 10.1002/anie.201908744
|View full text |Cite
|
Sign up to set email alerts
|

[3+2] Fragmentation of a Pentaphosphido Ligand by Cyanide

Abstract: The activation of white phosphorus (P4) by transition‐metal complexes has been studied for several decades, but the functionalization and release of the resulting (organo)phosphorus ligands has rarely been achieved. Herein we describe the formation of rare diphosphan‐1‐ide anions from a P5 ligand by treatment with cyanide. Cobalt diorganopentaphosphido complexes have been synthesized by a stepwise reaction sequence involving a low‐valent diimine cobalt complex, white phosphorus, and diorganochlorophosphanes. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 59 publications
5
52
0
7
Order By: Relevance
“…20) as well as on the anionic cobalt complex [(PHDI)Co(h 4 -P 4 )] À (D). 21 The reactivity of these complexes was only little investigated by the coordination chemistry of A and B towards coinage metal salts 18,22 and the reactivity of B towards Lewis acids as for instance B(C 6 F 5 ) 3 (Scheme 1). 18 The anionic compound D was quenched with phosphorus-based electrophiles (R 2 PCl) leading to neutral complexes with substituted cyclo-P 5 R 2 ligands (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20) as well as on the anionic cobalt complex [(PHDI)Co(h 4 -P 4 )] À (D). 21 The reactivity of these complexes was only little investigated by the coordination chemistry of A and B towards coinage metal salts 18,22 and the reactivity of B towards Lewis acids as for instance B(C 6 F 5 ) 3 (Scheme 1). 18 The anionic compound D was quenched with phosphorus-based electrophiles (R 2 PCl) leading to neutral complexes with substituted cyclo-P 5 R 2 ligands (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…18 The anionic compound D was quenched with phosphorus-based electrophiles (R 2 PCl) leading to neutral complexes with substituted cyclo-P 5 R 2 ligands (Scheme 1). 21 Ring expansion reactions were also reported for 1 using the pnictogenidene complexes [Cp*E{W(CO) 5 } 2 ] (E ¼ P, As), leading to neutral cobalt complexes with organo-Scheme 1 Reactivity of selected cyclo-P 4 ligand complexes. and [Cp*Ni(h 3 -P 3 )], 5,24 for which organo-substituted anionic complexes of the types [Cp*Fe(h 4 -P 5 R)] À and [Cp 000 Ni(h 2 -P 3 R)] À were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently,W olf and co-workersd escribed ah ighly selectiveP 4 functionalization and subsequentf ragmentation in the coordination sphere of ac obalt a-diimine complex (Scheme 21). [66] Ther eaction of the cyclo-P 4 cobaltate anion [LCo(h 4 bears bulky mesityl substituents, the reactionr eaches full conversion with only one equivalent of CN À .T he product in this case is 132,w hich features ar earranged P 5 Mes 2 ligand.T he authors suggested that similar cyclotetraphosphido complexesm ay be key intermediates in the fragmentations that ultimately lead to 130 and 131,but that the bulky mesityl substituent in 129 hinders such onward reactivity.…”
Section: Cyclo-p 4 Ligandsmentioning
confidence: 99%
“…Very recently, Wolf and co‐workers described a highly selective P 4 functionalization and subsequent fragmentation in the coordination sphere of a cobalt α‐diimine complex (Scheme 21). [66] The reaction of the cyclo ‐P 4 cobaltate anion [LCo(η 4 ‐P 4 )] − ( 128 , L=bis(2,6‐diisopropylphenyl)phenanthrene‐9,10‐diimine) with R 2 PCl (R=Cy, t Bu, Ph, Mes, N( i Pr) 2 ) quantitatively gives the neutral cyclo ‐P 5 R 2 complexes 129 in up to 77 % isolated yield. Depending on the substituent R, different reaction outcomes are observed upon treatment of 129 with cyanide salts ([K(18‐crown‐6)]CN, [Et 4 N]CN, [ n Bu 4 N]CN).…”
Section: Transition‐metal‐mediated Functionalization Of White Phosphorusmentioning
confidence: 99%
“…Die Folgechemie dieser anionischen Komplexe wurde bisher kaum untersucht. Verbindung C kann mit Chlorophosphanen gequencht werden, unter Bildung von neutralen Komplexen mit einem disubstituierten fünfgliedrigen P 5 R 2 ‐Liganden [4] . Verbindung A kann mit Elektrophilen reagieren, um, z.…”
Section: Introductionunclassified